Pancreaticopleural Fistula in Chronic Pancreatitis Patients: Risk Factors, Management, and Outcomes - Akhil, Sunkara (Journal of Neonatal Surgery, 2025)
Background: Pancreaticopleural fistula (PPF) is a rare complication of chronic pancreatitis, characterized by an abnormal communication between the pancreatic ductal system and the pleural cavity. Although the incidence is low, PPF is clinically significant due to the risk of recurrent pleural effusions, respiratory compromise, and associated morbidity. Identifying risk factors and timely management strategies is vital for optimizing outcomes. Methods: We conducted a retrospective analysis of patients with chronic pancreatitis who developed PPF over a 10-year period at a tertiary referral center. Patient data included demographic details, etiology of chronic pancreatitis, clinical presentation, imaging and laboratory findings, therapeutic interventions (endoscopic, surgical), and outcomes. Risk factors for PPF were assessed using logistic regression. Management approaches and post-treatment outcomes, including resolution of PPF and complications, were documented. Results: A total of 48 patients with chronic pancreatitis who presented with PPF were identified. The most common etiologies included alcohol-related pancreatitis (62%) and idiopathic chronic pancreatitis (25%). Recurrent episodes of severe pancreatitis and ductal disruptions were prominent risk factors. Endoscopic management, particularly pancreatic duct stenting, was successful in 73% of cases, while 20% required surgical intervention. The overall mortality rate was 8%, primarily due to severe comorbidities and advanced disease. Clinical resolution of PPF with resolution of pleural effusions occurred in 84% of patients. Conclusion: Pancreaticopleural fistula remains a challenging but treatable complication of chronic pancreatitis. Early recognition, aided by high clinical suspicion and imaging, is crucial. Endoscopic interventions provide favorable outcomes in most cases, reducing the need for major surgery. Optimizing the management of chronic pancreatitis and addressing modifiable risk factors may help reduce the incidence and improve long-term outcomes.